LEGAL VIEWS IN THE HOLY BOOK OF ZOROASTRIANISM "AVESTA" (American Journal of Pedagogical and Educational Research, 2023)
In this article, the author analyzes that the sacred book of Zoroastrian religion "Avesta" has the status of a legal-normative document, which is the basis for the formation of the moral image of society, in which human rights, crime and punishment, responsibility for actions, development of laws and regulations of mutual relations are developed. This aspect of the issue serves as additional material for learning not only the history of the state and law of Uzbekistan, but also the history of the state and law of foreign countries.